“Application of Fermatean Fuzzy Matrix in Co-Design of Urban Projects” - Derpich-Contreras, I; Sepulveda-Salas, J; Barraza-Alonso, R (Elsevier B.V., 2021)
This work presents a multiple criteria decision-making (MCDM) model based on Fermatean fuzzy sets (FFS) for solving a problem of citizen participation for collaborative decision making under the paradigm of Smart Cities. The model seeks to detect the preferences of decision makers in order to evaluate a set of project alternatives for improving the connectivity of the main road axes in the city of Santiago de Chile based on smart cities criteria. The project alternatives, criteria, linguistic decision variables, and the decision maker s evaluations are analyzed under a Fermatean fuzzy sets framework and judgments are expressed by Fermatean fuzzy linguistic numbers (FFLNs) in a decision matrix stating the values of the membership and non-membership degree. Then, the combined distance-based assessment method (CODAS) is applied to propose the best project. The main benefit of the proposed model is to reduce the time for the co-design of urban projects, thus ensuring better coverage of citizen participation. © 2021 The Authors. Published by Elsevier B.V.
Keywords: Fermatean Fuzzy Sets; Decision Making; Multi-criteria analysis; Smart-Cities